Investigação das condições ótimas de operação de um desodorizador industrial de óleo de soja na concentração de tocoferóis no destilado - Lemos, Flavio Luis (2013)
Soybean oil is recognized as an important nutritional source because of its high energy value and the presence of vitamins, essential fatty acids and natural antioxidants. Refining is the purification of the raw oil, being the stage deodorizing the process of vaporization of odorous compounds and free fatty acids, dragging them to the distillate and producing refined oil. The economic distillate deodorized soybean oil (DDSO) mainly depends on the composition and content of tocopherols presented in high demand for chemical and food industries. Once the operating conditions of the deodorizer based solely on the quality of refined oil, this dissertation aimed to investigate by computer simulation the optimum condition for processing tocopherols concentration in the distillate, while maintaining the quality of refined oil. Therefore, the mathematical model was developed with mass balance, energy and balance using the predictive empirical equations and models for calculating the physical properties of the blend components, and a convergence algorithm by the Newton-Raphson method. It was incorporated to balance the drag and mechanical efficiency of Murphree. To better characterize the behavior of the currents, the compositions studied were formed by triacylglycerol's (TAG), diacylglycerol's (DAG), monoacylglycerol's (MAG), free fatty acids (FFA) and tocopherols (TOC). The model was described for a continuous steady flow with cross current. Simulations were conducted to define the best operating condition that increases the concentration of tocopherols in DDSO. The next step was to validate these parameters in two deodorizers with industrial scale, comparing the results and verifying the achievement of goals. The differences between the proposed model and the results obtained in both plants were very good and fully met the business needs of companies.